2009
DOI: 10.1182/blood-2008-12-195941
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factors 1 and 2 are important transcriptional effectors in primary macrophages experiencing hypoxia

Abstract: Ischemia exists in many diseased tissues, including arthritic joints, atherosclerotic plaques, and malignant tumors. Macrophages accumulate in these sites and up-regulate hypoxia-inducible transcription factors (HIFs) 1 and 2 in response to the hypoxia present. Here we show that the gene expression profile in primary human and murine macrophages changes markedly when they are exposed to hypoxia for 18 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
270
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(279 citation statements)
references
References 46 publications
7
270
2
Order By: Relevance
“…Unlike p38 and c-Jun, ERK 1/2 phosphorylation levels were not enhanced by palmitate treatment under hypoxia. Severe hypoxia, less than 1% O 2 , has been shown to activate the NF-B signaling pathway in macrophages (26,27). However, in our experiments, exposure to 1% O 2 did not enhance the levels of palmitate-induced p-IB␣ compared with normoxia (data not shown).…”
Section: Hypoxia Enhances Palmitate-induced Pro-inflammatory Cytokinecontrasting
confidence: 64%
“…Unlike p38 and c-Jun, ERK 1/2 phosphorylation levels were not enhanced by palmitate treatment under hypoxia. Severe hypoxia, less than 1% O 2 , has been shown to activate the NF-B signaling pathway in macrophages (26,27). However, in our experiments, exposure to 1% O 2 did not enhance the levels of palmitate-induced p-IB␣ compared with normoxia (data not shown).…”
Section: Hypoxia Enhances Palmitate-induced Pro-inflammatory Cytokinecontrasting
confidence: 64%
“…Previously published studies using primary human macrophages have demonstrated that in normoxic macrophages HIF-2α but not HIF-1α plays a dominant role in regulating VEGF transcription (33) whereas hypoxic macrophages rely on both HIF-1α and -2α for VEGF expression (34). This is in contrast to our study where we detected a significant increase in Vegf and Glut-1 transcripts, but no detectable levels of Hif-2α or Epo transcripts in monocytes of our myeloid-specific Vhl KO mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although TRAP1 is reported to be up-regulated in some cancers, its expression is diminished in others (8,(37)(38)(39). The impact of reduced TRAP1 expression on in vitro cell invasion raises the possibility that certain more aggressive, metastatic, or late-stage cancers may express less TRAP1 than less advanced tumors.…”
Section: Trap1 Expression Correlates Inversely With Tumor Stage In Cementioning
confidence: 99%